EFFECTIVE WAYS OF TEACHING PAST TENSES IN THE ENGLISH LANGUAGE - Gafurjanova Ferangiz, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
This  article  examines  effective  methods  of  teaching  past  tenses  in  English, focusing on both theoretical and practical aspects of grammar instruction. It analyzes common  learner  difficulties,  including  confusion  between  tense  and  aspect,  and highlights strategies such as explicit explanation, inductive learning, storytelling, role-plays,  and  task-based  activities.  The  importance  of  corrective  feedback  and  the integration of digital tools are also discussed. The study concludes that a balanced approach combining accuracy and communicative practice is essential for successful mastery of past tense forms.